Impaired Volume Regulation is the Mechanism of Excitotoxic Sensitization to Complement - Loo, Li Shen (J Neurosci, 2006)
Previous work demonstrated that a brief, sublethal excitotoxic insult strikingly increased the sensitivity of cortical neurons to the cytotoxic effects of the terminal pathway of complement, a process termed “excitotoxic sensitization.” Here, we sought to elucidate the cellular mechanism of excitotoxic sensitization in embryonic rat cortical neurons in vitro. Excitotoxic sensitization did not increase membrane attack complex deposition on cortical neurons and produced only a small reduction of membrane attack complex removal, because of a selective decrease of endocytic elimination. Membrane attack complexes and other osmotic stressors, namely hypotonic stress and glutamate, induced transient swelling of cortical neurons, followed by return to normal volume despite persistence of the stressor, a homeostatic response termed regulatory volume decrease (RVD). A minimal excitotoxic insult impaired this homeostatic response and sensitized neurons to cytotoxic effects of diverse osmotic stressors. Structurally distinct membrane-impermeable osmolytes, dextran and polyethylene glycol, prevented excitotoxic sensitization to diverse osmotic stressors including membrane attack complexes. Paraquat, a reactive oxygen species generator, alone was sufficient to impair RVD, and MnTBAP [Mn(III)tetrakis(4-benzoic acid)porphyrin chloride], a reactive oxygen species scavenger, prevented excitotoxin-mediated impairment of RVD. Together, these findings demonstrate that impairment of RVD is the mechanism of excitotoxic sensitization, that reactive oxygen species alone are sufficient to impair RVD, and that reactive oxygen species are necessary for excitotoxic sensitization-mediated impairment of RVD.